Residential Services Criteria's in Iraq - عبد الرزاق, أ.م.د.نجيل كمال; امين, م.م.نادين نضال (Journal of Planner and Development, 2007)
Many studies and researches represented the importance of the planning and designing criteria's. Planning and Designing issue influence by three factors, firstly: The Present situation of life is always exchanging and developing. Secondly: Design work represents views of problem that never appear at the beginning of the work but only by plan implementation which need to in some cases to modifying the specify aims and criteria's. Thirdly: Never establish criteria's and aims that can be used as a reference before starting design and planning process. This research will study present situation of the services for residential areas criteria's and planning legitimate in some designed cities in Iraq with different levels (neighborhood, community and district) Finding the standardized and Criteria which will be useful for the designer and the planner, at the same time gives flexibility and the possibility to adaptation with the renewal situation for the design and    the planning process